2019
DOI: 10.1002/dc.24277
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound guided fine‐needle aspiration vs core needle biopsy for solid pancreatic lesions: Comparison of diagnostic accuracy and procedural efficiency

Abstract: Background: Endoscopic ultrasound (EUS) guided core needle biopsies (CNB) are increasingly being performed to diagnose solid pancreatic lesions. However, studies have been conflicting in terms of CNB improving diagnostic accuracy and procedural efficiency vs fine-needle aspiration (FNA), which this study aims to elucidate.Methods: Data were prospectively collected on consecutive patients with solid pancreatic or peripancreatic lesions at a single tertiary care center from November 2015 to November 2016 that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
(67 reference statements)
1
15
1
Order By: Relevance
“…EUS-FNB needles, on the other hand, allow sampling of a larger amount of tissue and better preservation of cell architecture than an aspirate. Several studies have shown comparable diagnostic accuracy of EUS-FNA and EUS-FNB in solid pancreatic lesions, with the exception of fewer needle passes needed to obtain an adequate sample using the EUS-FNB technique 8 9 10 11 . Recently Sweeney et al also showed comparable diagnostic yield of EUS-FNA, FNB, and combined FNA and FNB in solid pancreatic lesions 12 .…”
Section: Introductionmentioning
confidence: 99%
“…EUS-FNB needles, on the other hand, allow sampling of a larger amount of tissue and better preservation of cell architecture than an aspirate. Several studies have shown comparable diagnostic accuracy of EUS-FNA and EUS-FNB in solid pancreatic lesions, with the exception of fewer needle passes needed to obtain an adequate sample using the EUS-FNB technique 8 9 10 11 . Recently Sweeney et al also showed comparable diagnostic yield of EUS-FNA, FNB, and combined FNA and FNB in solid pancreatic lesions 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A combination of cytology and histology would give 85% accuracy with EUS‐FNA for solid pancreatic lesions (75.4%‐94.8% based on cytology and 68.9%‐89.3% based on histology alone), 6 with better outcomes with histology alone for those tumors that are not adenocarcinomas 18 . One report showed that the combination of cytology with core histology gave the same results as core histology alone 19 . However, other technical factors influence the diagnosis: for example, fanning with three passes using cytology and core histology assessment obtained better accuracy compared with conventional sampling (94% vs 77%) 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The included period ranged from 2012 to 2021. Eleven RCTs 13,[15][16][17][19][20][21]24,[26][27][28] were parallel trials and 7 14,18,22,23,25,29,30 were cross-over studies. Six RCTs were conducted in Asia 14,15,19,20,23,24 and all studies presented 2 well balanced arms regarding lesion features (location and size) and clinical demographical characteristics.…”
Section: Study Characteristicsmentioning
confidence: 99%